Microbiome composition of disturbed soils from sandy-gravel mining complexes with different reclamation approaches - Anastasiia Kimeklis; Grigory Gladkov; Rustam Tembotov; Arina Kichko; Alexander Pinaev; Sergey Hosid; Evgeny Andronov; Evgeny Abakumov (One Ecosystem, 2022)
Activities connected to mineral mining disrupt the soil layer and bring parent rock material to the surface. It leads to altering the environmental conditions and leaves behind vast areas of disturbed lands. Returning these lands to natural ecosystems is an important contemporary challenge, which can be acquired by reclamation practices. Soil microbiome composition reflects changes happening to disturbed lands; thus, its analysis is a powerful tool for evaluating the disturbance degree and estimating the effect of the implementation of reclamation techniques. Additionally, factors connected to the characteristics of a particular geographical region have a certain impact on the microbiome and should be taken into account. Thereby, studies of soil microbiomes of disturbed soils of different origins are essential in understanding the dynamics of soil restoration. Here, we focus on soil microbiomes from two sandy-gravel mining complexes in mountainous areas with a moderate continental climate of the Central Caucasus. These quarries share the same parent rock material, but differ in benchmark soil type and reclamation approach - one was left for passive recovery and the other was technically reclaimed with overburden material. Comparative analysis of microbiome composition, based on sequencing of 16S rRNA gene libraries, showed that region and disturbance are the key factors explaining microbiome variation, which surpass the influence of local factors. However, the application of reclamation techniques greatly reduces the dissimilarity of soil microbiomes caused by disturbance. Linking of soil chemical parameters to microbiome composition showed that the disturbance factor correlates with a lack of organic carbon. Other chemical parameters, like pH, ammonium, nitrates and total carbon explain microbiome variability on a smaller scale between sampling sites. Thus, while regional and disturbance factors reflected differentiation of soil microbiomes, soil chemical parameters explained local variation of certain groups of microorganisms.